TENSILE STRENGTH AND FIBRINOGEN YIELD IN FIBRIN GLUE PREPARATIVES WITH AND WITHOUT FREEZE-DRYING METHOD - Brilliant Margalin; S. P. Edijanto; Paulus B. Notopuro (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Fibrin glue is a useful biological product to stop bleeding, adhesive tissue and accelerate wound healing. Preparation of Fibrin Glue requires fibrinogen and thrombin components. The routine cryoprecipitation method performed at the Blood Bank can be used to improve the quality of the fibrinogen component. The Freeze Drying process can increase the retention time of plasma products at room temperature. Yield Fibrinogen and Tensile Strength is a quantitative and qualitative parameter of preparation quality of fibrin glue. This study focused on finding differences between Tensile Strength and Yield Fibrinogen on fibrin glue preparative by cryoprecipitate with and without freeze drying methods.This study is in vitro laboratory experiments design by comparing the Yield Fibrinogen and Tensile Strength of fibrin glue preparation from cryoprecipitic plasma with and without freeze dried process. The results were analyzed comparatively using paired T test.The plasma fibrinogen content of the sample was 237.66 ± 67.10 mg / dL. The fibrinogen content of the cryoprecipitate component without freeze drying process was 327.74 ± 103.42 mg / dL with a yield fibrinogen of 1.38 ± 0.25. The fibrinogen content of the cryoprecipitate component with freeze drying process was 251.20 ± 103.91 mg / dL with yield fibrinogen 1.04 ± 0.25. Tensile strength of fibrin glue from cryoprecipitate without freeze drying process was found to average 0.52 ± 0.18. Tensile strength of fibrin glue from cryoprecipitate with freeze drying process was found to average 0.33 ± 0.12. There was a significant difference between yield fibrinogen and tensile strength of fibrin glue preparation of cryoprecipitation method with and without freeze dried process.There is a significant difference on yields fibrinogen and tensile strength in the preparation of fibrin glue by the freeze drying process which is probably due to changes in the structure and function of fibrinogen proteins.